Experimental and Numerical Investigation of DARPA Suboff Submarine Propelled with INSEAN E1619 Propeller for Self-Propulsion - Ozden, Yasemin Arikan; Ozden, Munir Cansin; Demir, Ersin; Kurdoglu, Sertac (SOC NAVAL ARCHITECTS & MARINE ENGINEERS, 2019)
The Defense Advanced Research Projects Agency (DARPA) Suboff Submarine propelled by the Italian Ship Model Basin (INSEAN) E1619 propeller is extensively used in submarine validation studies. Although there are several numerical studies where the DARPA Suboff submarine is used in combination with E1619 propeller there are no experimental data available in open literature for the self-propulsion condition. In this article, the self-propulsion characteristics of the DARPA Suboff submarine model with INSEAN E1619 propeller obtained with experimental and numerical methods are presented and discussed by means of Taylor wake fraction, thrust deduction, hull efficiency, relative rotative efficiency, and propulsive efficiency. To experimentally investigate the submarine form, a self-propulsion experimental setup is designed and manufactured. Resistance and self-propulsion experiments are conducted in Istanbul Technical University Ata Nutku Ship Model Testing Laboratory. Resistance tests are carried out for three different speeds, and the results show good agreement with the published experimental results. Propulsion tests are conducted by using the load-varying self-propulsion test method for constant speed and seven different propeller rotation rates. Rotational speed, thrust, and torque forces at self-propulsion point are investigated. For the numerical computations a commercial Computational Fluid Dynamics (CFD) code is used. Propeller open water characteristics and nondimensional velocities behind the propeller are calculated. Self-propulsion point of the submarine and propeller assembly is also solved numerically and the results are compared with the results obtained from the experiments, and it is seen that especially the propeller rate of revolution and thrust force are predicted with very good approximation.
Keywords: submarine; DARPA Suboff; self propulsion; EFD; CFD; E1619; propeller; SIMULATION; FLOW; Engineering